2018
DOI: 10.1093/ehjqcco/qcy041
|View full text |Cite
|
Sign up to set email alerts
|

Association between process performance measures and 1-year mortality among patients with incident heart failure: a Danish nationwide study

Abstract: Meeting process performance measures, which reflect care in concordance with clinical guideline recommendations, was associated with substantially lower 1-year mortality among patients with incident HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…Improvements in prognosis over years among Danish HF patients have been reported previously . However, changes in other factors apart from pharmacological treatment may have influenced the prognosis, including changes in the risk profile of the patients and improved non‐pharmacological treatment …”
Section: Discussionmentioning
confidence: 72%
“…Improvements in prognosis over years among Danish HF patients have been reported previously . However, changes in other factors apart from pharmacological treatment may have influenced the prognosis, including changes in the risk profile of the patients and improved non‐pharmacological treatment …”
Section: Discussionmentioning
confidence: 72%
“…14,20 For example, in a Danish nationwide study, researchers used echocardiography, New York Heart Association classification, treatment with ACEI/ARB, β-blockers, physical training and patient education to construct a composite process performance measure to represent overall quality of HF care, and found the association between performance measures and 1-year mortality that followed a doseresponse pattern. 20 In our study, 90 day and 1 year mortality rates of 10.8% and 21.0%, respectively, were observed in patients hospitalized in secondary hospitals, almost twice the corresponding rates of people hospitalized in tertiary institutions (90 day mortality: 5.0%; 1 year mortality: 12.1%). After controlling individual-level confounders, patients admitted to tertiary hospitals had a 51% lower risk of 90 day death and a 39% lower risk of 1 year mortality death.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with a recent systematic review of systems of care for HF patients, which concluded that a suite of interventions led by a HF specialist workforce are needed across the continuum of care 11 . Quality improvement projects that improve compliance with guidelines have been shown to improve survival and readmission rates 12‐15 . We chose to implement intervention with evidence of improved outcomes, including comprehensive post‐discharge support, 16 a HF care bundle, 17 an early follow‐up clinic, 18 nurse‐led medication titration and patient education 19,20 …”
Section: Discussionmentioning
confidence: 69%